Critique, social media and the information society - Sandoval, Marisol; Fuchs, Christian, 1976- (Routledge studies in science, technology and society ;, 2014)
"Now more than ever, we need to understand social media - the good as well as the bad. We need critical knowledge that helps us to navigate the controversies and contradictions of this complex digital media landscape. Only then can we make informed judgments about what's happening in our media world, and why.